2016
DOI: 10.1108/jfra-06-2015-0065
|View full text |Cite
|
Sign up to set email alerts
|

Board diversity and corporate social responsibility in Jordan

Abstract: Purpose This study aims to investigate the impact of board diversity characteristics, namely, independence, gender, age and nationality of directors on the level of corporate social responsibility (CSR) disclosures. Design/methodology/approach Content analysis was used to determine CSR disclosure. This study used panel data analysis to investigate the influence of board diversity characteristics on CSR disclosures. Findings Panel data analysis show that the level of CSR disclosure has increased over the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
239
14
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 202 publications
(332 citation statements)
references
References 54 publications
27
239
14
11
Order By: Relevance
“…The average female board member is 3% percent, with a minimum value of zero and a maximum value of 56 percent. This finding supports the figures reported by previous works done in Jordan such as Ibrahim and Hanefah (2016) and Al-Rahahleh (2017). But, this finding is lower than that reported in previous studies such as Garcí a-Sá nchez et al (2017) in Spain who found that 10% of board seats under dominance female.…”
Section: Descriptive Statisticssupporting
confidence: 93%
See 4 more Smart Citations
“…The average female board member is 3% percent, with a minimum value of zero and a maximum value of 56 percent. This finding supports the figures reported by previous works done in Jordan such as Ibrahim and Hanefah (2016) and Al-Rahahleh (2017). But, this finding is lower than that reported in previous studies such as Garcí a-Sá nchez et al (2017) in Spain who found that 10% of board seats under dominance female.…”
Section: Descriptive Statisticssupporting
confidence: 93%
“…Regarding the average age, the findings report that the average directors' age is approximately 52.8 years, with a maximum age of (71) years, and a minimum of (35) year, this finding is consistent with Sartawi et al (2014) who found that the average age of directors is 57 years. Moreover, the average young members is around (12 %) (Younger than 40, as suggested by Ibrahim and Hanefah (2016), this implies that most of board members in Jordan are elderly.…”
Section: Descriptive Statisticsmentioning
confidence: 90%
See 3 more Smart Citations